2020
DOI: 10.13057/biodiv/d220106
|View full text |Cite
|
Sign up to set email alerts
|

The potential of amylase enzyme activity against bacteria isolated from several lakes in East Java, Indonesia

Abstract: Abstract. Nisa IK, Prabaningtyas S, Lukiati B, Saptawati RT, Rodiansyah A. 2021. The potential of amylase enzyme activity against bacteria isolated from several lakes in East Java, Indonesia. Biodiversitas 21: 42-49. Indonesia is one country that has water resources having an abundance of microbial diversity, but not explored massively. This study aims to measure the amylase activity quantitatively from 53 amylolytic bacterial isolates from Ranu Pani, Ranu Regulo, Ranu Grati, and Ngebel Lake; also it identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…AL3.11 isolate has a 99.53% similarity with Bacillus paramycoides strain MCCC 1A04098. According to Nisa et al (2021), Bacillus paramycoides bacteria found in Ngebel Lake was also known to produce amylase. Microorganisms can produce amylase enzymes, especially from the Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…AL3.11 isolate has a 99.53% similarity with Bacillus paramycoides strain MCCC 1A04098. According to Nisa et al (2021), Bacillus paramycoides bacteria found in Ngebel Lake was also known to produce amylase. Microorganisms can produce amylase enzymes, especially from the Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The amylase activity value at day 0 is quite high, this might be due to the measurement of the enzyme activity using the DNS method, in which reduc- ing sugar formed from a carbon source (starch) is used by bacteria for the initial stages of growth; then, the bacteria will use the carbon source for the production of enzymes. The amylase activity of Bacillus cereus KN isolated from Ranu Ngebel and incubated for three days was 0.016 U/mL, while strain G20 isolated from Ranu Grati was lower at about 0.0001 U/mL (Nisa et al 2021). Luang et al ( 2019) found Bacillus sp.…”
Section: Crude Enzyme Production Of a Selected Isolate And Measuremen...mentioning
confidence: 99%
“…The measurement of reducing groups produced by the different enzymes was performed using the 3,5dinitro salicylic acid (DNS) technique (Nisa et al, 2021). The choice of standard for enzyme analysis depended on the specific kind of enzyme being studied.…”
Section: Quantifying Enzymatic Activitymentioning
confidence: 99%